Investigation of chemosensitivity during and after an acute cold. Issue 2 (7th November 2016) - Pellegrino, Robert; Walliczek‐Dworschak, Ute; Winter, Gudrun; Hull, David; Hummel, Thomas
Abstract : Background: Viral rhinitis (the "common" cold) is a frequent worldwide disease. Olfactory dysfunction is one complication that arises during infection, which in most cases heals up spontaneously upon recovery, whereas in some cases it may persist as a partial or total loss of olfaction. The aim of this prospective study was to investigate the change of other chemosensory systems during a cold. Methods: Fifty‐eight patients (age 18 to 69 years) with an acute cold were compared to a healthy control group (n = 59; age 19 to 63 years). All patients were examined on 2 occasions separated by approximately 4 weeks. Orthonasal, retronasal, gustatory, and trigeminal nasal function were investigated. Furthermore, ratings of real foods, in terms of intensity and pleasantness, were obtained. Results: Compared to the control group, patients showed a decreased orthonasal (threshold and discrimination) and retronasal function. Furthermore, patients exhibited a decreased sensitivity to salt and a reduced ability to localize menthol, indicating a decreased taste and trigeminal function, respectively. Upon recovery from the infection, orthonasal olfactory and trigeminal sensitivity increased, whereas retronasal sensitivity showed no improvement and salt sensitivity decreased. Conclusion: This comprehensive study provides empirical evidence that chemosensory impairment is prevalent during a cold, and additionally shows for the first time that chemosensory features associated with food consumption persist postinfection.